PEJAMAS : PENDIDIKAN KESEHATAN REPRODUKSI REMAJA DENGAN MEDIA ANIMASI PADA SANTRI PUTRI DI SMP NURUL JADID PONDOK PESANTREN NURUL JADID - Yusri Dwi Lestari; Manisah Salma; Vidia Khoirunnisak; Icha Monica Amalia Irfandi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Adolescence period is a very critical period, during which adolescenct are very vulnerable to various reproductive health problems. Limited knowledge and understanding can lead adolescents towards risk behavior. Lack of knowledge about reproductive health, the importance of maintaining the cleanliness of reproductive organs, and the impact of irresponsible behavior causes some teenagers to experience health problems. Reproductive health behavior in adolescence is very important in determining the future of adolescents. Adolescent reproductive behavior will lead to reproductive risks, including the risk of unwanted pregnancy, abortion, HIV/AIDS, reproductive tract disorders, and psychosexual disorders due to sexual behavior. This condition shows that reproductive health information is very important for adolescents. The purpose of this activity is to provide adolescent reproductive health education for female students at the junior high school level at the Nurul Jadid Islamic Boarding School. The media used in the form of leaflets and animation of adolescent reproductive health. The result of this activity is an increase in knowledge about adolescent reproductive health